Problems on English Word Stress Placement Made by Indonesian Learners of English - Sukardi Weda (Hasanuddin University, 2018)
AbstractThis study focuses its investigation on the problems of stress placement in English words made by Indonesian learners of English (ILE). The subjects of the study were the students of English Literature Study Program Universitas Negeri Makassar (N = 66, 20 or 30.30% males and 46 or 69.69 females). Results of the study show that the Indonesian learners of English (ILE) were able to put the an acute accent (´) illustrating the primary stress on monosyllabic words (one syllable words) easily; two syllable words, except for word permit; three syllable words, except for the word determine; words with suffixes in reading test; words with prefixes, except for word imbalance; compound words, except for word sunrise; noun phrases; stress on verbs and stress on nouns. The ILE were not able to put an acute accent (´) illustrating the main stress on polysyllabic words with suffixes in written test, but the ILE has excellent competence for the words objectivity and disagreement. The ILE therefore tended to put the correct stress placement on reading test than on written test. The ILE often mistress the words in polysyllabic words, like: permit, determine, imbalance, accuracy, anchorage, etc. Additionally, descriptive statistics shows the percentage of correct and incorrect pronunciation made by Indonesian Learners of English (ILE) in recording and written test. The educational implication of this study is that the practice for stress placement of words, ranging from monosyllabic words to polysyllabic words needs to be taught in English learning and teaching process in the classroom setting. This in keeping with the results of the questionnaires that ‘Learning correct stress placement needs large portion in EFL classroom’ with a mean 3.6061 and SD = .87493 and ‘Correct stress placement on words is important’ with a mean of 4.1515 and SD = .68483. Keywords: Pronunciation problems, stress, stress placement, English, ILE